2010
DOI: 10.1128/jb.00568-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Enzymes Encoded by the Anthrose Biosynthetic Operon of Bacillus anthracis

Abstract: Bacillus anthracis spores, the etiological agents of anthrax, possess a loosely fitting outer layer called the exosporium that is composed of a basal layer and an external hairlike nap. The filaments of the nap are formed by trimers of the collagenlike glycoprotein BclA. Multiple pentasaccharide and trisaccharide side chains are O linked to BclA. The nonreducing terminal residue of the pentasaccharide side chain is the unusual sugar anthrose. A plausible biosynthetic pathway for anthrose biosynthesis has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…The Cps2L product was confirmed to be dTDP-Glc by its retention time, which was similar to that of the standard dTDP-Glc. The Cps2N and Cps2M reaction products had a delayed retention time compared to that of their precursors, similar to other dTDP-keto intermediates analyzed with these methods (16). The shorter retention time for the Cps2O product relative to dTDP-Glc is consistent with that reported for dTDPRha in other publications (23,50).…”
Section: Resultssupporting
confidence: 80%
“…The Cps2L product was confirmed to be dTDP-Glc by its retention time, which was similar to that of the standard dTDP-Glc. The Cps2N and Cps2M reaction products had a delayed retention time compared to that of their precursors, similar to other dTDP-keto intermediates analyzed with these methods (16). The shorter retention time for the Cps2O product relative to dTDP-Glc is consistent with that reported for dTDPRha in other publications (23,50).…”
Section: Resultssupporting
confidence: 80%
“…These data provide proof of concept for the antigenicity of the exosporium anthrose trisaccharide as a marker of B. anthracis spore exposure and infection. Future studies will evaluate enhanced analytic sensitivity of the anti-ATS antibody detection assay and determine the diagnostic sensitivity and specificity of the anti-ATS antibodies and their utility as a diagnostic tool (7,19). Collectively these data will contribute to our ability to quickly detect exposure to B. anthracis spores.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inactivation of gene BAS3322 resulted in spores with about half as much anthrose as found in wild-type spores (6). Furthermore it was reported that inactivation of gene BAS3321 resulted in BclA being substituted with trisaccharides only, suggesting that the enzyme is a dTDP-␤-L-rhamnose ␣-1,3-L-rhamnosy transferase that attaches the fourth residue of the pentasaccharide side chain (7). Inactivation of genes BAS3320 and BAS3319 resulted in the disappearance of BclA pentasaccharides and the appearance of a tetrasaccharide lacking anthrose (7).…”
mentioning
confidence: 94%